Chronic heart failure - J. A. Ker (South African Family Practice)
Heart failure is a global problem. It is estimated that approximately 38 million people worldwide experience heart failure, and this number is growing because of the ageing of nations’ populations, but also because patients are rescued from death during an acute myocardial infarction, and later develop heart failure. The prevalence of heart failure is roughly 2% of the population, and up to 10% in people aged 75 years and older. It is also estimated that the lifetime risk of heart failure at the age of 40 years is approximately 20% (one in five) for both men and women. Heart failure is also increasing in low- and medium-income countries, probably because of changes in lifestyle which favour the development of obesity, hypertension and diabetes mellitus. The mortality of heart failure is worse than that associated with most cancers. Average mortality is roughly 50% within five years. However, evidence-based treatment did reduce mortality significantly. About two thirds of the economic burden of heart failure is owing to hospital admissions and re-admissions. Therefore, heart failure is also an expensive disease.